2020
DOI: 10.1186/s12882-020-01761-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of chronic kidney disease and diabetic kidney disease in a central Chinese urban population: a cross-sectional survey

Abstract: Background: This study was conducted to evaluate and update the current prevalence of and risk factors for chronic kidney disease (CKD) and diabetic kidney disease (DKD) in a central Chinese urban population. Methods: From December 2017 to June 2018, a total of 5231 subjects were randomly enrolled from 3 communities in 3 districts of Zhengzhou. CKD was defined as estimated glomerular filtration rate (eGFR) < 60 mL/min.1.73m 2 or urinary albumin to creatinine ratio ≥ 30 mg/g (albuminuria). Diabetic subjects wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 50 publications
1
30
2
3
Order By: Relevance
“… 14 , 15 Indeed, while only 1.6% of our COVID-19 patients had a previous history of chronic kidney diseases, 30.8% had a history of DM and 30.4% had a history of hypertension, in which both were considered major risk factors for the development of chronic kidney disease and reduced eGFR. 16 …”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 Indeed, while only 1.6% of our COVID-19 patients had a previous history of chronic kidney diseases, 30.8% had a history of DM and 30.4% had a history of hypertension, in which both were considered major risk factors for the development of chronic kidney disease and reduced eGFR. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when uric acid is present in the cytoplasm of cells or in the acidic/hydrophobic environment of atherosclerotic plaques, it is converted to a pro-oxidant, and it promotes oxidative stress, including cardiovascular disease through this mechanism, participating in the pathophysiology of human disease [21]. Recent studies reported that hyperuricemia is an independent predictor of CKD [22,23]. Uric acid concentration is an independent risk factor for kidney failure in earlier stages of CKD and has a J-shaped relationship with all-cause mortality in CKD [24].…”
Section: Discussionmentioning
confidence: 99%
“…При этом отмечаются определенные различия в распространенности в разных частях мира. По обобщенным результатам 19 популяционных исследований из 13 европейских стран скорректированная распространенность ХБП 1-5 стадий варьировала от 3,31% (3,30-3,33%) в Норвегии до 17,3% (16,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18),1%) в северо-восточной Германии, скорректированная распространенность ХБП 3-5 стадий варьировала от 1,0% (0,7-1,3%) в центральной Италии до 5,9% (5,2-6,6%) в северо-восточной Германии [5]. Распространенность ХБП С1-5 в Восточной Африке составляет 6,8% (5,7-8,1%) и варьирует по регионам: 12,5% (10,1-15,4%) в восточной части Уганды, 3,9% (2,2-6,8%) на юго-западе Уганды и 3,7% (2,7-5,1%) в западной Кении [6].…”
Section: распространенность хронической болезни почекunclassified
“…Распространенность ХБП С1-5 в Восточной Африке составляет 6,8% (5,7-8,1%) и варьирует по регионам: 12,5% (10,1-15,4%) в восточной части Уганды, 3,9% (2,2-6,8%) на юго-западе Уганды и 3,7% (2,7-5,1%) в западной Кении [6]. Распространенность ХБП С1-5 в центральном Китае составляет 16,8% (15,8-17,8%) [7]. В Российской Федерации (РФ) по результатам московского исследования распространенность ХБП С1-5 составила 4% общей популяции, из которых 4,8% были пациентами с ХБП С4-5 [8].…”
Section: распространенность хронической болезни почекunclassified